Scaling-Stimulated Salivary Antioxidant Changes and Oral-Health Behavior in an Evaluation of Periodontal Treatment Outcomes. (3rd November 2014) - Yang, Po-Sheng; Huang, Wei-Chen; Chen, Shyuan-Yow; Chen, Chien-Hsun; Lee, Chang-Yu; Lin, Che-Tong; Huang, Yung-Kai
Abstract : Aim . Our goal was to investigate associations among scaling-stimulated changes in salivary antioxidants, oral-health-related behaviors and attitudes, and periodontal treatment outcomes. Materials and Methods . Thirty periodontitis patients with at least 6 pockets with pocket depths of >5 mm and more than 16 functional teeth were enrolled in the study. Patients were divided into three groups: an abandoned group (AB group), a nonprogress outcome group (NP group), and an effective treatment group (ET group). Nonstimulated saliva was collected before and after scaling were received to determine superoxide dismutase (SOD) and the total antioxidant capacity (TAOC). Results . Salivary SOD following scaling significantly increased from 83.09 to 194.30 U/g protein in patients who had irregular dental visit patterns (<1 visit per year). After scaling, the TAOC was significantly higher in patients who had regular dental visits than in patients who had irregular dental visits (3.52 versus 0.70 mmole/g protein, P < 0.01 ). The scaling-stimulated increase in SOD was related to a higher severity of periodontitis in the NP group, while the scaling-stimulated increase in the TAOC was inversely related to the severity of periodontitis in the AB group. Conclusions . These results demonstrate the importance of scaling-stimulated salivary antioxidants as prognostic biomarkers of periodontal treatment.